Analisis Ketimpangan Pembangunan dan Pertumbuhan Ekonomi di Provinsi Gorontalo - Mopangga, Herwin (Jurnal Trikonomika, 2011)
This study aims to analyze the change of economic structure; development imbalances resulting from the proportional imbalance in GDRP per capita, Human Development Index and Infrastructure Expenditure Ratio; form of relationship development and inequality of economic growth and to provide policy recommendations. The analysis is using Williamson Index, Gini Ratio, Shift-Share, Klassen Typhology and Regression of Unbalanced Panel. The results showed that although growth was lower than the non-agriculture but agriculture is still dominant in the economic structure. Potentially sector and the greatest economic growth occurs in regions of secondary and tertiary sector that have occurred indicate a shift in economic structure in the Province of Gorontalo during the period 2001-2008. Pohuwato Regency and Gorontalo Municipality has a competitive economic, including in Quadrant I on matrix typology Klassen (high growth and high income), while Boalemo, Gorontalo Regency and Bone Bolango in the Quadrant III (low growth and low income). Simultaneously and partial, the difference of all independent variable are significant as the main source of inequality.